The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.24323/akademik-gida.1187023
|View full text |Cite
|
Sign up to set email alerts
|

Production of Iced Tea from Poppy Flowers Extract

Abstract: Iced teas, which are among the drinks that are frequently consumed today, are mostly produced from black tea and the production of iced teas of different plant origins is very limited. Poppy plant (Papaver rhoaes L.) is an annual edible flower species belonging to the family Papaveraceae, and it has been stated in various studies that the anthocyanins it contains have bioactive properties such as anti-inflammatory, antimicrobial and antiproliferative. In this study, poppy flower anthocyanins were obtained by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…51 It is stated that dried poppy flower contains 48.09 ± 0.31 mg GAE/g. 3 In parallel with our study, Aydogdu et al detected a significant decrease in the concentration of the total phenolic components during the storage period. In general, it is thought that the decrease in phenolic content may be related to changes in the polymerization of phenolic compounds.…”
Section: Analysis Of Phenolic Compounds During Storagesupporting
confidence: 91%
See 4 more Smart Citations
“…51 It is stated that dried poppy flower contains 48.09 ± 0.31 mg GAE/g. 3 In parallel with our study, Aydogdu et al detected a significant decrease in the concentration of the total phenolic components during the storage period. In general, it is thought that the decrease in phenolic content may be related to changes in the polymerization of phenolic compounds.…”
Section: Analysis Of Phenolic Compounds During Storagesupporting
confidence: 91%
“…Phenolic compounds have antioxidant, antimicrobial, and anti-inflammatory effects. It has also been reported that it is used in the treatment of diseases such as obesity, cancer, and diabetes. ,, It has been reported that poppy and bee bread are rich in phenolic components and bee bread is a functional food. ,, …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations